Translating evidence and interpreting testimony at a war crimes tribunal : working in a tug-of-war - Elias-Bursać, Ellen, 1952- (New York : Palgrave Macmillan, 2015)
"How can defendants be tried if they cannot understand the charges being raised against them? Can a witness testify if the judges and attorneys cannot understand what the witness is saying? Can a judge decide whether to convict or acquit if she or he cannot read the documentary evidence? The very viability of international criminal prosecution and adjudication hinges on the massive amounts of translation and interpreting that are required in order to run these lengthy, complex trials, and the procedures for handling the demands facing language services. This book explores the dynamic courtroom interactions in the International Criminal Tribunal for the Former Yugoslavia in which witnesses testify--through an interpreter--about translations, attorneys argue--through an interpreter--about translations and the interpreting, and judges adjudicate on the interpreted testimony and translated evidence"--
Introduction -- Part I: The translators and interpreters -- 1. The practitioners -- 2. The practice -- 3. Practicalities -- Part II: The courtroom -- 4. The witnesses -- 5. The office of the prosecutor -- 6. The defence -- 7. Chambers and the ICTY legacy -- 8. Conclusion.
Includes bibliographical references (pages 286-296) and index.
Keywords: Court interpreting and translating; War crime trials; Conduct of court proceedings; Translators -- Legal status, laws, etc; Law -- Translating; Translating and interpreting